Evaluatıon of Technologıcal Development Indıcators ın Kazakhstan Under Industry 4.0 - Azretbergenova, G.; Nakhipbekova, S.; Turysbekova, G. (Economic series of the Bulletin of L.N. Gumilyov ENU, 2022)
The understanding of the fourth industrial revolution is important in determining the direction in Kazakhstan according to the fourth industrial revolution. On the way to the list of 50 developed countries, it is important to assess the level of readiness of Kazakhstan in terms of technological infrastructure for Industry 4.0. This article covers the effects of the process of Industry 4.0, the so-called smart manufacturing, which constitutes the fourth generation of the industrial revolution, and the factors influencing this process. In addition, in this study, the types of technological products that can be evaluated in the framework of Industry 4.0 for the economy of Kazakhstan and the created economic value are studied. In this context, the impact of scientific research and education on technological changes and transformation was studied as the most important direction. Thus, it is possible to draw a conclusion about the development process of the Industry 4.0 period of Kazakhstan. In order to fundamentally change the economy of our country, it is intended to create competitive industries, and it is possible to achieve a competitive economy by introducing technologies and science into production.